Compilation of Spatial Models in Improving the Performance of Maintenance of Irrigation Area Networks in Purwodadi and Brati Districts, Grobogan - Soedarsono S; Selvia Agustina (Universitas Islam Sultan Agung, 2021)
The Grobogan Regency Government, apart from constructing and maintaining weir buildings and dams that function to divide irrigation water, also continues to strive in developing the Secondary Irrigation Area Network. However, until now the handling of the construction and maintenance of the Irrigation Network carried out by the Department of Public Works and Spatial Planning of Grobogan Regency has not been able to be carried out optimally because there are several obstacles faced, including limited geographic / spatial-based data and information that is accurate as a tool for know the location of the Irrigation Network infrastructure and the supporting buildings for the Irrigation Network. The purpose of this research is to implement a Geographical Information System (GIS) application using the ArcGis program, to compile an information system in the form of a data base for the Irrigation Area network and to determine the priority for the maintenance of the Irrigation Area network using the following parameters: how much area is the Irrigation Area network irrigated, how long is the irrigation area canal damage and how much it costs to maintain the irrigation network The inventory data of the irrigation area network is obtained from the Irrigation and Raw Water sector of the PUPR Service of Grobogan Regency, this data is in the form of existing irrigation area network data, As-built Drawing images from the implementation results and photos of the location of the irrigation area network.